The Effect of Iodine-Containing Nano-Micelles, FS-1, on Antibiotic Resistance, Gene Expression and Epigenetic Modifications in the Genome of Multidrug Resistant MRSA Strain Staphylococcus aureus ATCC BAA-39 - Reva, Oleg N.; Korotetskiy, Ilya S.; Joubert, Monique; Shilov, Sergey V.; Jumagaziyeva, Ardak B.; Suldina, Natalya A.; Ilin, Alexandr I. (Frontiers in Microbiology, 2020)
Application of supplementary drugs which increase susceptibility of pathogenic bacteria to antibiotics is a promising yet unexplored approach to overcome the global problem of multidrug-resistant infections. The discovery of a new drug, an iodine-containing nano-molecular complex FS-1, which has proven to improve susceptibility to antibiotics in various pathogens, including MRSA strain Staphylococcus aureus ATCC BAA-39TM, allowed studying this phenomenon. Chromosomal DNA and total RNA samples extracted from the FS-1 treated strain (FS) and from the negative control (NC) cultures were sequenced by PacBio SMRT and Ion Torrent technologies, respectively. PacBio DNA reads were used to assemble chromosomal DNA of the NC and FS variants of S. aureus BAA-39 and to perform profiling of epigenetically modified nucleotides. Results of transcriptional profiling, variant calling and detection of epigenetic modifications in the FS variant were compared to the NC variant. Additionally, the genetic alterations caused by the treatment of S. aureus BAA-39 with FS-1 were compared to the results of a similar experiment conducted with another model organism, E. coli ATCC BAA-196. Several commonalities in responses of these phylogenetically distant microorganisms to the treatment with FS-1 were discovered, which included metabolic transition towards anaerobiosis and oxidative/osmotic stress response. S. aureus culture appeared to be more sensitive to FS-1 due to a higher penetrability of cells by iodine bound compounds, which caused carbonyl stress associated with nucleotide damaging by FS-1, abnormal epigenetic modifications and an increased rate of mutations. It was hypothesized that the disrupted pattern of adenine methylated loci within methicillin-resistance chromosome cassettes (SCCmec) may promote excision of this antibiotic resistance determinant from chromosomes while the altered pattern of cytosine methylation was behind the adaptive gene regulation in the culture FS. The selection against the antibiotic resistance in bacterial populations caused by abnormal epigenetic modifications exemplifies possible mechanisms of antibiotic resistance reversion induced by iodine-containing compounds. These finding will facilitate development of therapeutic agents against multidrug-resistant infections.